Residents’ happiness indicators living in Borobudur Temple, Central Java - Dewanti, Diah Setyawati; Purnomo, Sigit (Technium Social Sciences Journal, 2022)
Borobudur temple is one of the seven wonders of World-Heritage. Community who live surround in Borobudur temple is increasing year by year, and lessm migration cases. This research aims to analyze the definition of happiness from the perspective of well-being concept according to residents surrounding tourism spots. Second, to analyze the indicators of local residents’ happiness indicators to well-being concept from tourism activities. Third, to analyze the impact of the development of Borobudur Temple tourist attractions on local residents to the well-being concept. The research subjects are local residents who already live and work in the Borobudur temple area. Data collection methods used are observation, interviews, and documentation. The data obtained through interviews and documentation studies. The results of the research analysis show that the thoughts regarding the definition of happiness for local residents in Borobudur Temple area get various their own thoughts including the Happiness in the definition of comfortable and calm life, Happiness in the definition of accepting whatever has been obtained from God (Gratitude), Happiness in the definition of family, Happiness in the definition of controlling happiness itself, Happiness in the view of well-being in the definition of not being in debt and having a lot of money, and happiness in the view of subjective well-being. Then, there is a positive relationship resulting from the indicators of happiness which are influenced by financial and also happiness which is influenced by environmental factors. Finally, the impact of tourism development greatly affects the lives of local residents and Key Informants in this study.